Document Management System Development Building Division Mahasarakham University - Wongphombute, Jirasak (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
The objectives of the research article were to document management system development, track the process of repair and convenience in tracking documents or official documents protected with lost or dispatch process. The researchers designed and tested by real users 35. And satisfaction of the users of the system for managing documents survey. The device used to collect the information is a interview form and questionnaire. The statistics used in this research are mean and standard deviation. The research found that the users were satisfied with the system for managing documents at a high level, because the system can effectively operate as intended. Which help in tracking documents more easily. Enables operational efficiency, flexibility, more convenience. The introduction of computer technology used to administer a substance to include the retention of data communication within the organization, also reduces the amount of paper use. Space and location in the store. Users can communicate through a computer screen, making it more rapid pace with demand. Information is more accurate cost of the organization in the long run. Reducing time and steps in performance resulting operational efficiency even more. The research feedback from users of the system requirements, design and development of management documents to respond to the needs of users to the achievement of the operation. Building Division University next.